2011
DOI: 10.3384/ecp110571182
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectricity Power Generation from Organic Substrate in a Microbial Fuel Cell Using Saccharomyces Cerevisiae as Biocatalysts

Abstract: In recent years, as a novel mode of converting organic matter into bioelectricity, Microbial fuel cells (MFCs) have gained significant attention. Among effective parameters in MFCs, substrate type and concentration play major role on MFC performance. In this study, a dual chamber MFC was used with a wide range of fructose concentrations: 10, 20 30 and 40 g/l. The MFC was inoculated with Saccharomyces cerevisiae as biocatalyst. A100µm of neutral red as mediator and also 100µm ferricyanide as oxidizer added to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Using Ohm's law (V = I × R), current was calculated, using P = V × I, power generation was calculated 9 ; further, this current and power generation was normalized to the anode surface area to calculate current density (mA/m 2 ) and power density (mW/m 2 ). Open circuit voltage was computed directly by connecting the anode and cathode wires to the data acquisition system.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Ohm's law (V = I × R), current was calculated, using P = V × I, power generation was calculated 9 ; further, this current and power generation was normalized to the anode surface area to calculate current density (mA/m 2 ) and power density (mW/m 2 ). Open circuit voltage was computed directly by connecting the anode and cathode wires to the data acquisition system.…”
Section: Measurementsmentioning
confidence: 99%
“…For electrical power generation, external resistor of 250 Ω was connected to the anode and cathode wires, and voltage drop was measured across the arms of resistor. Using Ohm's law (V = I × R), current was calculated, using P = V × I, power generation was calculated 9 ; further, this current and power generation was normalized to the anode surface area to calculate current density (mA/m 2 ) and power density (mW/m 2 ). Coulombic efficiency was calculated using the same external resistor based on changes in COD concentration.…”
Section: Measurementsmentioning
confidence: 99%
“…Several studies have shown that MFCs operating with mixed cultures achieve comparatively more power densities than those operated with pure cultures . High power generation with pure culture is possible, but in such cases the cultures were grown externally and the same device was not used in acclimatized mixed cultures .…”
Section: Microbial Fuel Cells System Performance With Pure Microbial mentioning
confidence: 99%
“…Several studies have shown that MFCs operating with mixed cultures achieve comparatively more power densities than those operated with pure cultures. 9,16,51 High power genera-D Bose, M Gopinath, P Vijay Perspective: Sustainable Power generation from Wastewater sources using Microbial Fuel Cell Shewanella and Geobacter species. Similar exploration with graphite electrodes in a dairy wastewater-sediment interface reported an OCV of around 800 mV with current and power density as 68 × 10 −6 mA cm −2 and 53 × 10 −6 mW cm −2 .…”
Section: Microbial Fuel Cells System Performance With Pure Microbial mentioning
confidence: 99%
See 1 more Smart Citation